Teaching arithmetic operations in elementary grades - Rashidxon Uulu Atabek; Zohidova Zarnigor Sodiqjon qizi (Genius Journals, 2024)
State education is encouraged to create equal opportunities for each of the standard students in education, to encourage each of them to achieve high results, and thereby to ensure a different organization of the educational process. The production of state educational standards by subject, by field of education, based on the selection of the variant of the subject, implies the improvement of educational methodical complexes, including mathematics teaching in primary classes. Arithmetic operations in elementary grades serve to ensure the internal connection of academic subjects and the intercohesion of academic subjects based on the principle of connection and coordination of knowledge. Fulfillment by students of the requirements of performing arithmetic operations in elementary grades helps them acquire all the necessary knowledge, skills and abilities.
Keywords: Arithmetic operation; methodology; task; science